Language, culture and cognition: a study on requests in Italian, Brazilian Portuguese, Argentinian Spanish and German (PERcursos Linguísticos, 2020)
Starting from the premise that language is not just a code made of grammar structures and lexical forms, but a product of human cognition encompassing linguistic, cultural and cognitive schemata, in this study we set out to understand how these categories emerge from language, by analysing requests in Italian, Brazilian Portuguese, Argentinian Spanish and German from a cross-cultural pragmatic perspective. In particular, we focused our analyses on how (in)directness and conventionality were linguistically realized in head acts and, concurrently, on which perspectives were used, namely whether requests were speaker-oriented, hearer-oriented, inclusive or impersonal (BLUM-KULKA; HOUSE; KASPER, 1989). We hypothesized that, by observing requests from this perspective, we could verify the presence of analogies and differences in linguistic and cultural traits. While some analogies were observed, with the four languages sharing a preference for intermediary positions in the speaker’s choices, there also emerged differences that point to peculiarities in each culture.